Preparation Of Financial Reports of Non - Profit Organizations Based on ISAK NO 35 (Case Study of the Catholic Church in Sidamanik) - Marintan Saragih; Djahotman Purba; Reynaldi Nainggolan (Program Studi Akuntansi Universitas Simalungun, 2024)
This research is motivated by the situation of the Catholic Church in Sidamanik which presents financial reports in the form of cash in and cash out manually. The aim of this research is to prepare financial reports for the Catholic Church in Sidamanik based on ISAK number 35 concerning the presentation of financial reports for non-profit oriented organizations. This type of research is descriptive qualitative with data collection techniques in the form of documentation and interviews. The data analysis technique in this research goes through the stages of data reduction, data presentation and drawing conclusions. In analyzing the data, an accounting cycle is implemented which will produce financial reports in accordance with ISAK 35, namely Income Reports and Net Asset Change Reports. The results of this research indicate that the Catholic Church in Sidamanik presents financial reports in the form of cash in and cash out manually in the form of handwriting which is not in accordance with the presentation regulated in ISAK number 35. The financial reports of the Catholic Church in Sidamanik which have been prepared by the author based on ISAK 35 present five financial reports, namely Income Report and Net Asset Change Report